Anticoagulation Drugs the Current State of the Art - Kelleni, Mina (IntechOpen, 2020)
In this book, you'll find the latest updates about the current use of anticoagulants in medical practice. This includes clinical pharmacotherapy, laboratory monitoring, and antidotes. You'll also find a special focus on heparin-induced thrombocytopenia, including various mechanisms and presentations. Finally, you'll find important details that will help you to understand what patients receiving anticoagulants know about these drugs and how to improve their quality of life.